Design and develop universal underactuated gripper - Chau, Oscar Jia Liang (Nanyang Technological University, 2021)
This project presents an underactuated tendon-driven robotics gripper that is capable of picking and placing daily objects. Due to its compliant property, such grippers allow the ease of gripping without much extensive planning, reducing mechanical and control complexity. Unlike traditional hard link grippers, tendon-driven grippers are safer as they are passive compliant where they can bend upon impact. In this project, an alternative differential mechanism is created to adapt to three fingers grasping. Unlike other differential mechanisms that use two layers of pulley system, this differential mechanism is more compact and easily assembled. With a single input, it can drive three output motion. The prototype demonstrated can perform two grasping modes: spherical and tripod gripping for daily objects. However, its capacity to carry a heavier load can be improved further. Recommendation for improvements and future work are included in chapter 6.